Linux network administrator´s guide - Kirch, Olaf (O'Reilly, 2000)
The Linux Network Administrator's Guide, updates a classic Linux title from O'Reilly. This refreshed resource takes an in-depth look at everything you need to know to join a network. Topics covered include all of the essential networking software that comes with the Linux operating system, plus information on a host of cutting-edge services including wireless hubs, spam filtering, and more.